The History and Diversity of Rice Domestication as Resolved From 1464 Complete Plastid Genomes - He, Wenchuang; Chen, Caijin; Xiang, Kunli; Wang, Jie; Zheng, Ping; Tembrock, Luke R.; Jin, Deming; Wu, Zhiqiang (Frontiers in Plant Science, 2021)
The plastid is an essential organelle in autotrophic plant cells, descending from free-living cyanobacteria and acquired by early eukaryotic cells through endosymbiosis roughly one billion years ago. It contained a streamlined genome (plastome) that is uniparentally inherited and non-recombinant, which makes it an ideal tool for resolving the origin and diversity of plant species and populations. In the present study, a large dataset was amassed by de novo assembling plastomes from 295 common wild rice (Oryza rufipogon Griff.) and 1135 Asian cultivated rice (Oryza sativa L.) accessions, supplemented with 34 plastomes from other Oryza species. From this dataset, the phylogenetic relationships and biogeographic history of O. rufipogon and O. sativa were reconstructed. Our results revealed two major maternal lineages across the two species, which further diverged into nine well supported genetic clusters. Among them, the Or-wj-I/II/III and Or-wi-I/II genetic clusters were shared with cultivated (percentage for each cluster ranging 54.9%∼99.3%) and wild rice accessions. Molecular dating, phylogeographic analyses and reconstruction of population historical dynamics indicated an earlier origin of the Or-wj-I/II genetic clusters from East Asian with at least two population expansions, and later origins of other genetic clusters from multiple regions with one or more population expansions. These results supported a single origin of japonica rice (mainly in Or-wj-I/II) and multiple origins of indica rice (in all five clusters) for the history of rice domestication. The massive plastomic data set presented here provides an important resource for understanding the history and evolution of rice domestication as well as a genomic resources for use in future breeding and conservation efforts.